Phosphodiesterase 2A2 regulates mitochondria clearance through Parkin-dependent mitophagy - Lobo, MJ; Reverte-Salisa, L; Chao, Y; Koschinski, A; Subramaniam, G; Zaccolo, M (Nature Research, 2020)
Programmed degradation of mitochondria by mitophagy, an essential process to maintain mitochondrial homeostasis, is not completely understood. Here we uncover a regulatory process that controls mitophagy and involves the cAMP-degrading enzyme phosphodiesterase 2A2 (PDE2A2). We find that PDE2A2 is part of a mitochondrial signalosome at the mitochondrial inner membrane where it interacts with the mitochondrial contact site and organizing system (MICOS). As part of this compartmentalised signalling system PDE2A2 regulates PKA-mediated phosphorylation of the MICOS component MIC60, resulting in modulation of Parkin recruitment to the mitochondria and mitophagy. Inhibition of PDE2A2 is sufficient to regulate mitophagy in the absence of other triggers, highlighting the physiological relevance of PDE2A2 in this process. Pharmacological inhibition of PDE2 promotes a ‘fat-burning’ phenotype to retain thermogenic beige adipocytes, indicating that PDE2A2 may serve as a novel target with potential for developing therapies for metabolic disorders.